Compost from municipal solid wastes as a source of biochar for CO2 capture - Karimi, Mohsen (2020)
ncreasing greenhouse gas emissions contributing to the global climate change are a major concern of environmental protection. Developing adsorbents from low-cost and renewable resources is an attractive strategy. On the other hand, the high capacity of production rates of municipal solid waste, besides high methane emissions, is the origin of some eco-systemic challenges. The combination of the two environmental problems is considered by introducing the compost from a mechanical biological treatment of municipal solid wastes as a low-cost source of adsorbent for CO2 capture. The obtained compost was thermally and chemically activated and the CO2 adsorption capacities of prepared samples were evaluated. Samples prepared sequentially with sulfuric acid and heated at 800 degrees C and vice versa, respectively, had the highest uptake capacities and were comparable with commercial adsorbents.